Styles of stress coping in drug dependent patients - Guevara Ortega, Gilmar (2001)
In the present investigation the confrontation styles are studied to the stress used by patient drug dependence that are receiving treatment in Therapeutic Communities of Metropolitan Lima. The sample is formed by 88 patients that have dependence problems to substances psychoactive like alcohol, pastures basic of cocaine, hydrochlorate of cocaine and marihuana. The instrument used for the present investigation is the Questionnaire COPE, elaborated by Carver, Scheir and Weintraub in 1989, this questionnaire allows to evaluate the forms or confrontation styles that people use before stressful events. The psychometric analysis was carried out by means of the correlation article-test corrected, it implies that the article is compared with the test without including. The consistency goes into it established using the coefficient of dependability Alpha of Cronbach.